Toxemic and complex immune syndromes in patients with malignant cerebral neoplasms - R. Yu. Seliverstov; V. Ye. Olyushin; V. A. Shatrov; A. F. Gurchin (Бюллетень сибирской медицины)
The goal of the research was studying the key mechanisms of pathogenesis of toxemic and complex immune syndromes in patients with malignant cerebral neoplasms, and also studying the possible ways of correction of such syndromes.